PEMUNGUTAN PAJAK DI INDONESIA - Purnamawati, Evi (Solusi, 2017)
Tax imposition among tax subjects is balanced with ability that is balanced with the income they enjoy under government protection. The tax levied must be based on the law so as to ensure the legal certainty, both for tax authorities as tax collectors and taxpayers as taxpayers. The research method using the normative research type, the result of the discussion of tax collection should be done sehemat (as efficiently) not to the cost of tax levy greater than the tax revenue itself. The system used in taxes through 3 (three) are: Official assessment system, self assessment system with holding system, factors that hinder tax levies in Indonesia, lack or absence of public awareness, centralized central government authority in the supervision of local tax collection, the preparedness of the region in handling the tax dispute, the granting of licenses, the recommendations and the execution of public services that are less or incompatible with the scope of its duties, the tax conclusions are paid by the taxpayer at maturity or when conducting taxable taxable items managed by the Central Government there are also taxes levied by the Provincial Government either District or District / City, Provincial Tax and City District. Lack of citizens' awareness of the obligation to pay taxes even some taxes are perceived as coercive for citizens.